Comparison of Fluticasone Furoate Nasal Spray Versus Combined Oral Anti-Histamine and Anti-Leukotriene Therapy in Allergic Rhinitis - Junaid Shahzad, Sadia Chaudhry, Mohammad Moaz Aslam , Amir Akbar , Maidah Hanif , Junaid Shahzad, Sadia Chaudhry, Mohammad Moaz Aslam , Amir Akbar , Maidah Hanif (Journal of Rawalpindi Medical College, 2018)
Background:.To compare intranasal Fluticasone furoate spray with oral anti-histamine and anti-leukotriene therapy in allergic rhinitis in terms of change in mean nasal symptoms score. Methods: In this randomized control trial two groups were selected having 40 patients in each group. To group (A) cetirizine 10 mg plus montelukast 10 mg once daily was prescribed and to group (B) Fluticasone Furoate nasal spray 110 mcg once daily was prescribed for 6 months.Patients were called for follow up visits 4 times, 1st after 2 weeks then after every two months. On every follow-up visit .Total nasal symptoms scores were registered. Final outcome was measured on 4th visit. Results: After six months follow up, the minimum total nasal symptom score was calculated as 0.50 and maximum total nasal symptom score was calculated as 2.88 with mean + SD as 1.62 + 0.69. There were 45% male and 55% were female. In group A, the mean +SD was 2.21 + 0.38 whereas in group B the mean +SD was 1.04 + 0.33. Significant difference was found between study groups for the AR having p-value 0.001.Significant difference of mean change in symptoms was found in both groups with p-value = 0.000 in age group < 40 years. In age group > 40 years, significant difference of mean change in symptoms was found in both groups with p-value = 0.000. Conclusion: Fluticasone furoate nasal spray was more effective than combined oral anti-histamines and leukotriene receptor antagonists in allergic rhinitis.